Radial aplasia and chromosome 22q11 deletion. Issue 11 (November 1997) - Digilio, M C; Giannotti, A; Marino, B; Guadagni, A M; Orzalesi, M; Dallapiccola, B
Abstract : We report on a neonate with deletion 22q11 (del22q11) presenting with facial dysmorphism, ocular coloboma, congenital heart defect, urogenital malformations, and unilateral radial aplasia. This malformation complex includes features frequently occurring in velocardiofacial syndrome as well as findings described in the CHARGE and VACTERL associations. To our knowledge, the present case is the first report of radial aplasia in del22q11. This observation further supports and extends the clinical variability of del22q11.